The Nexus Between University Support and Entrepreneurial Mindset: Does Entrepreneurship Education Matter? - Cahyani, Utari Evy; Hanafi, Syafiq Mahmadah; Masruri, Siswanto (School of Business, IPB University (SB-IPB), 2022)
This study intends to analyze the nexus between university support and an entrepreneurial mindset. This study also analyzes the mediating role of entrepreneurship education in this relationship. The research subjects are Public Islamic higher education (PTKIN) students who have participated in entrepreneurship education programs. The data in this study were collected using an online questionnaire. The number of respondents in this study was 297 students. Entrepreneurship education and entrepreneurial mindset are dependent variables and university support is an independent variable. Data analysis by Partial Least Square-Structural Equation Modeling (PLS-SEM). The results define that university support has a positive effect on entrepreneurship education and entrepreneurial mindset. Entrepreneurship education also has a positive effect on the entrepreneurial mindset. In addition, entrepreneurial mindsets mediate the relationship between university support and entrepreneurial mindsets. The implication of this finding is to enhance the students’ entrepreneurial mindset, PTKIN must provide support for an entrepreneurship education program for students. PTKIN needs to develop a university-based entrepreneurial ecosystem. Keywords: social cognitive theory, entrepreneurship ecosystem, entrepreneurship education, entrepreneurial mindset, undergraduate students